Desenvolvimento de revestimentos para embalagens celulósicas baseados em amido modificado e celulose microfibrilada - Scheffer, Mayara (2022)
The use of paper in food packaging presents itself as an alternative to the extensive use of plastic. Due to the cellulose hydrophilic and porous character, synthetic polymers coatings are commonly applied to provide better mechanical and barrier properties to paper packaging. In this context, coatings based on a combination of biopolymers and nanomaterials have been studied because of their biodegradability, wide availability, non-toxicity and ability to improve paper surface characteristics. Thus, the aim of this study is to develop coatings composed by a matrix of modified starch (hydroxypropyl di-starch phosphate - HDSP) and glycerol (GLY), with micro fibrillated cellulose (MFC) as a reinforcing agent, and apply them in Kraft paper samples. A Central Composite Rotational Design (CCRD) was employed in the experiment design to study the impact of the control variables (%MFC, %GLY and %HDSP) on the response variables – suspension viscosity, tensile strength, permeability to oils and fats and coating homogeneity. After data collection, the Analysis of Variance (ANOVA) and the Response Surface Methodology (RSM) were used as statistical tools to analyze the behavior of the responses in face of variations in the compositions of the treatments. Although the experimental data hasn’t presented adequacy to the proposed model, as they presented R2 lower than 0,85, it was possible to observe that, regardless of the composition, (i) the suspensions presented a pseudoplastic fluid behavior; (ii) high levels of HDSP combined with intermediate levels of MFC showed adequate viscosity results and reflected in high resistance to oils and fats (kit number above 8) and a greater coatings uniformity; (iii) and weights lower than 20 g/m2 produce better results in tensile strength and worse results in barrier properties. At the end of the research, Kraft papers coated with suspensions based on modified starch and micro fibrillated cellulose nanocomposites with high potential for application as packaging were produced. Coating prepared on Run 8 presented the biggest highlight, since it showed the highest resistance against oil and grease (kit number = 12) and excellent homogeneity results, being recommended as fast consumption food packaging and with high grease content.